Análisis productivo y económico de la crianza de pollos broiler en pequeña escala, en el recinto Cascajal, cantón Cumandá, provincia de Chimborazo - Tenecota Chuquizala, Carlos Valentín (2017)
The research called productive and economic analysis of small broiler broiler breeding in Cascajal, Canton Cumandá, province of Chimborazo had as objectives: to carry out a situational diagnosis of the production of boiler chickens on farms located in the Cascajal Precinct, To determine the profitability of the broiler chickens for fattening, to elaborate a technical management plan for the broiler broiler breeding and to socialize the results with the producers of the Cascajal Precinct. The methods used were the scientific, deductive and analytical method which allowed me to implement investigative techniques such as observation and the application of surveys directed to each of the producers whose data collected by the owner allowed to obtain detailed information on the economic and productive situation Of the poultry farm of Cascajal. This investigative work allows us to know that the poultry activity in the sector is carried out with limited technical knowledge of management and biosafety even though 50% have been in this activity for three years. The production system is simi-intensive, producing chickens with intervals of 20 days between sheds with capacity of 1000 chickens each. 70% receive financing from food distributors; This activity is complementary to the agricultural one in 60%, the labor is familiar in a 100%, its facilities in an 80% are constructed with materials of the zone like the cane of guadua for the pillars with earth floor and ceiling Of zinc and it is important to note that 70% does not have a correct orientation of the shed (from East to West) which makes it difficult to control environmental factors. Biosecurity is another limitation for good production because there are no entrance showers, disinfection bowls or pediluviums within the general facilities. The disinfection of facilities and equipment is performed by 70% but only prior to the entry of the baby chick. Respiratory diseases occur in 100% of installations. Only 20% use curtain management to control the ammoniacal concentration that influences the mortality of 6% and 7% according to production data. Furthermore, they do not have a correct and adequate vaccination program. According to 80% of the producers, the market is still in constant demand despite the fact that prices are very unstable and fluctuate between $ 0.70 and $ 0.95 a pound of standing chicken. Stood at $ 0.85 compared to a cost of production of $ 0.84 per pound, obtaining a cost benefit of 1,009 and the profitability of 0.96 considered as loss. Facing this problem, a proposal for technical management of facilities, equipment, food, health and commercialization is presented, which will allow a return of 14.62% with an equal sale price of $ 0.85 a pound of standing chicken. It is concluded that the production of poultry in the sector is not profitable, because it is not managed in a technical way. Therefore it is recommended to implement the technical management proposal for the production of broiler chickens.